If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 2.3n + -11 = 4 + n Reorder the terms: -11 + 2.3n = 4 + n Solving -11 + 2.3n = 4 + n Solving for variable 'n'. Move all terms containing n to the left, all other terms to the right. Add '-1n' to each side of the equation. -11 + 2.3n + -1n = 4 + n + -1n Combine like terms: 2.3n + -1n = 1.3n -11 + 1.3n = 4 + n + -1n Combine like terms: n + -1n = 0 -11 + 1.3n = 4 + 0 -11 + 1.3n = 4 Add '11' to each side of the equation. -11 + 11 + 1.3n = 4 + 11 Combine like terms: -11 + 11 = 0 0 + 1.3n = 4 + 11 1.3n = 4 + 11 Combine like terms: 4 + 11 = 15 1.3n = 15 Divide each side by '1.3'. n = 11.53846154 Simplifying n = 11.53846154
| -2(10-9x)-6x+17= | | -5(-7x+2)=165 | | 6.1c+8=7.1c-3 | | 8(r+3)-3(3r-3)=30 | | 2x+5=75 | | 2x-18+18=84+18 | | 3(4x+3)=9x | | 2=3(4n-6)+8(5n-4) | | 4t-7=10t+5 | | 4x+3-5=29 | | x^2-x+6= | | 6x+7=42-x | | -9=-(1+8x)-2(4-4x) | | 7+x=.5(4*-2) | | 12x-4=5x-32 | | 3x+5+2x=54 | | 7x+20= | | 2x^2-17x+15=0 | | 5y+3=9y-1 | | 7+x=.5(4*2) | | 5x-1=3x+13 | | 5-4k=-(4k+1) | | 6x-12+3x+26=180 | | z^2(x+1)-3z(x+1)-70(x+1)=0 | | (1.1+k)5-7.6=1.6 | | d-4=-13 | | -2(w-7)+lOw=34 | | 7x+2y=7 | | 17+3(z+2)-11z=-7(z+2)+14 | | 20x+53= | | 2p-(1+8p)=4p-21 | | (15-y)+2=2y |